Design of Automatic Watering System Based on Arduino - Prasojo, Ipin; Maseleno, Andino; tanane, Omar; Shahu, Nishith (Universitas Muhammadiyah Yogyakarta, 2020)
Food self-sufficiency is a government program that has been being actively promoted so that Indonesia can reach food independence by the end of 2019. Indonesia is a maritime country and also an agricultural country with two seasons namely rainy season and dry season. In the rainy season, food plants usually do not need to be watered, while in the dry season, the plants must be watered regularly in accordance with soil moisture conditions. Farmers usually do not grow food plants in the dry season for fear that it will not grow well. The farmer’s dependence on the season causes the production to decline and becomes an obstacle in the success of the food self-sufficiency program. An information and communication technology-based agricultural device is needed to overcome the problem. The research aimed to design a programmed microcontroller chip to control watering automatically based on soil moisture detected using a domestic soil moisture sensor. This device detects whether the soil is dry or not. The farmers do not need to do watering manually. In addition to helping farmers, the device can also be installed on plantations, seedbed nurseries, urban parks, hotels, offices, and in homes that have parks or plants that need regular watering.